2016
DOI: 10.1002/jmri.25490
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of gadolinium deposition in dentate nucleus using quantitative susceptibility mapping

Abstract: PurposeGadolinium deposition in dentate nucleus (DN) has been reported after serial administration of gadoliniumbased contrast agents (GBCAs). Gadolinium complexes have paramagnetic properties, therefore, we evaluated susceptibility changes of gadolinium deposition in dentate nucleus (DN), using quantitative susceptibility mapping (QSM) for patients after serial administration of GBCAs. Materials and Methods48 patients with brain tumors, who had had serial GBCA administrations (GBCA group), and 48 healthy volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…QSM acts as a useful computer algorithm for deriving sensitivity values to iron levels from appropriate MRI data [ 17 , 55 ]. However, QSM detects paramagnetic substances, such as Zn2+, Cu2+, Ca2+, Fe3+, and gadolinium ions, and several studies have reported that the magnetic susceptibility of the globus pallidus and dentate nucleus increased after serial administration of gadobutrol [ 56 , 57 ]. The high abundance and high susceptibility of cellular iron compounds make iron the major biometal source for tissue QSM [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…QSM acts as a useful computer algorithm for deriving sensitivity values to iron levels from appropriate MRI data [ 17 , 55 ]. However, QSM detects paramagnetic substances, such as Zn2+, Cu2+, Ca2+, Fe3+, and gadolinium ions, and several studies have reported that the magnetic susceptibility of the globus pallidus and dentate nucleus increased after serial administration of gadobutrol [ 56 , 57 ]. The high abundance and high susceptibility of cellular iron compounds make iron the major biometal source for tissue QSM [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We looked at the presence of intralesional cystic components and intralesional hemorrhage as these have been reported as independent factors predicting the risk of rapid tumor growth and risk stratification for operative management of vestibular schwannomas. [2][3][4][8][9][10]12,17,18,20,22 There may be additional imaging features which impact clinical management that are not addressed in this study. Although this study was conducted in a large cohort of patients with vestibular schwannomas, the number of schwannomas that demonstrated intralesional hemorrhage was infrequent (5 patients).…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative method based on susceptibility mapping has recently been studied and used by other groups. 22 Third, our study did not include an age-matched control cohort of patients who did not receive any GBCA. However, each patient in our study cohort was followed serially across time, thus serving as his or her own internal control.…”
Section: Discussionmentioning
confidence: 99%